Pengaruh Struktur Modal, Manajemen Laba dan Ukuran Perusahaan Terhadap Agresivitas Pajak - Desti Ratnasari; Adhitya Putri Pratiwi (CV. ITTC INDONESIA, 2025)
This study aims to determine the effect of capital structure, earnings management, and company size on tax aggressiveness. The population in this study were primary consumer goods sector companies (consumer non cyclical) listed on the Indonesia Stock Exchange for the period 2019-2023 with a total sample of 38 companies for 5 years that met the predetermined criteria from a total of 190 companies and using a sampling technique, namely Purposive Sampling. The analysis used is multiple linear regression analysis and data processing is carried out with the help of Eviews 12 software. The results showed that simultaneously capital structure, earnings management, and company size affect tax aggressiveness. Partial research results show that capital structure has no effect on tax aggressiveness, earnings management has a negative effect on tax aggressiveness, and company size has a negative effect on tax aggressiveness. Keywords: Tax Aggressiveness, Earnings Management, Capital Structure, Company Size.